Worldwide post‐marketing safety surveillance experience with tofacitinib in ulcerative colitis. Issue 3 (9th October 2021) - Rubin, David T.; Modesto, Irene; Vermeire, Séverine; Danese, Silvio; Ng, Siew C.; Kwok, Kenneth K.; Koram, Nana; Jones, Thomas V.
Summary: Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of ulcerative colitis (UC). Post‐marketing surveillance (PMS) is an important part of monitoring adverse events (AEs). Aims: To report an analysis of PMS case safety reports for tofacitinib in patients with UC Methods: Worldwide tofacitinib PMS reports received in the Pfizer safety database from 30 May 2018 (first regulatory approval) to 25 August 2020 were analysed. The type and estimated reporting rate (RR) of serious AEs of interest, including infection, gastrointestinal, vascular, respiratory, neoplasm and cardiac events, were reviewed. Patient‐years of exposure (PY) was estimated based on worldwide sales data and the calculated daily regimens of tofacitinib 5 or 10 mg twice daily, immediate‐ or extended‐release formulations. Results: During the 27‐month reporting period, worldwide post‐marketing exposure to tofacitinib was 8916 PY. Overall, 4226 case reports were received and included 12 103 AEs, of which 1839 were serious AEs (SAEs). Among the cases reported, 1141 (27.0%) included an SAE and 18 (0.4%) were fatal. The RR (per 100 PY) for SAEs of interest by Medical Dictionary for Regulatory Activities System Organ Class were 3.28 for infections, 1.26 for vascular disorders, 0.74 for respiratory disorders, 0.55 for neoplasms and 0.50 for cardiac disorders. Conclusions: The types of AEs were consistent with those reported in tofacitinib clinical trials. Most reported AEs were non‐serious. Limitations of PMS reports and reliance on estimated RRs due to lack of precise values for exposure, required for incidence rate calculation, should be considered when interpreting these results. Abstract : Worldwide tofacitinib post‐marketing safety reports received in the Pfizer safety database from 30 May 2018 (first regulatory approval) to 25 August 2020 were analysed. The type and estimated reporting rate of serious adverse events of interest, including gastrointestinal, infection, vascular, respiratory, neoplasm and cardiac events, were reviewed. Patient‐years of exposure was estimated based on worldwide sales data. The types of adverse events and reporting rates were consistent with the known tofacitinib safety profile.